Laminate and manufacturing method thereof

JP7640345B2Active Publication Date: 2025-03-05DAIKYONISHIKAWA CORP
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2021065097
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-04-13
Filing Date
2021-04-07
Publication Date
2025-03-05
Estimated Expiration
2041-04-07

AI Technical Summary

Benefits of technology

【0016】 本開示によれば、透明性、硬度及び耐摩耗性に優れる積層体を提供すること、およびその製造プロセスが減圧を必要とせず、短時間で製造でき、低コストである積層体の製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007640345000005
    Figure 0007640345000005
  • Figure 0007640345000006
    Figure 0007640345000006
  • Figure 0007640345000007
    Figure 0007640345000007
Patent Text Reader

Abstract

To provide a laminate which is excellent in transparency, hardness and abrasion resistance, and a method for manufacturing a laminate which has a manufacturing process that dispenses with pressure reduction, can be manufactured for short time, and is inexpensive.SOLUTION: A laminate 1 has a plastic base material 10 and a laminated film 20. The laminated film 20 has a resin cured film 21 and a silicon oxide film 22 provided on a surface of the resin cured film 21, the resin cured film 21 has inorganic crystal particles having an average particle size of 10-100 nm, the inorganic crystal particles 30 are dispersed locally to the side of the silicon oxide film 22 and further exists on an interface between the resin cured film 21 and the silicon oxide film 22, and the inorganic crystal particles 30 (30A) existing on the interface is fit into the silicon oxide film 22.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a laminate in which a coating layer is formed on the surface of a substrate made of a plastic material, and a method for producing the same. [Background technology]

[0002] Development is underway to replace window glass for vehicles such as automobiles, trains, and aircraft with plastic window materials (hereinafter referred to as resin glazing) in order to reduce weight for the purpose of improving fuel efficiency and safety. A major challenge in changing from glass to plastic is to impart hardness, scratch resistance, and abrasion resistance similar to glass while maintaining high transparency. To address the above challenge, a method of coating a hard film made of a silicone resin on a transparent and strong polycarbonate resin (PC) substrate has been widely implemented (see, for example, Patent Document 1 or Patent Document 2). In addition, a method has been proposed in which an acrylic resin primer is formed as an intermediate layer on a PC substrate, and a silica film layer is formed thereon by a plasma CVD method to produce a transparent and abrasion-resistant laminate (see, for example, Patent Document 3).

[0003] Furthermore, in order to apply low-cost film formation under atmospheric pressure to automobile glazing materials having large areas and three-dimensional shapes, a remote atmospheric pressure plasma method that allows a large distance from the plasma nozzle is generally required (see, for example, Patent Document 4 or Patent Document 5). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 1-306476 [Patent Document 2] JP 2002-36870 A [Patent Document 3] JP 2009-67049 A [Patent Document 4] JP 2010-209281 A [Patent Document 5] JP 2016-199797 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, as in Patent Document 1 or Patent Document 2, the resin glazing having a silicon-based resin hard film does not have sufficient hardness and abrasion resistance as a resin glazing for automobiles. In addition, a long period of heat curing is required at a temperature that the plastic substrate can withstand, and there are also major issues in terms of time and cost required for production. As in Patent Document 3, a laminated film in which a silica thin film is formed by a plasma CVD method via a primer does not have sufficient abrasion resistance and scratch resistance as a resin glazing for automobiles. Furthermore, since a reduced pressure is required, there is a problem that a large amount of equipment cost and film formation time are required. Also, as in Patent Document 4 or Patent Document 5, the existing remote atmospheric pressure plasma method has not been able to obtain a material that satisfies the abrasion resistance and scratch resistance required for an automobile glazing material.

[0006] The present disclosure aims to provide a laminate having excellent transparency, hardness and abrasion resistance, and to provide a method for producing the laminate, the production process of which does not require reduced pressure, can be produced in a short time, and is low cost. [Means for solving the problem]

[0007] The laminate according to the present invention is a laminate having a plastic substrate and a laminate film, the laminate film having a cured resin film and a silicon oxide-based film provided on a surface of the cured resin film, The silicon oxide film has a thickness of 0.05 to 1.00 μm, The cured resin film contains inorganic crystal particles having an average particle size of 10 to 100 nm, the inorganic crystal particles being locally dispersed on the silicon oxide-based film side and further present at the interface between the cured resin film and the silicon oxide-based film, and the inorganic crystal particles present at the interface being embedded in the silicon oxide-based film.

[0008] In the laminate according to the present invention, the cured resin film preferably contains silicone oil. The inorganic crystal particles are more likely to be localized on the silicon oxide film side, and more particles are embedded in the silicon oxide film, so that the adhesion between the cured resin film and the silicon oxide film is improved. As a result, the hardness and abrasion resistance of the laminate film can be further improved.

[0009] In the laminate according to the present invention, the silicon oxide-based film is preferably a plasma vapor deposition film formed under normal pressure. By plasma vapor deposition under normal pressure, the cured resin film is etched, and inorganic crystal particles contained in the cured resin film are partially exposed, so that more particles are embedded in the silicon oxide-based film, and the adhesion between the cured resin film and the silicon oxide-based film is improved. As a result, the hardness and wear resistance of the laminate film can be improved.

[0010] In the laminate according to the present invention, it is preferable that the silicon oxide film contains oxygen atoms and silicon atoms, and further contains at least one of carbon atoms, hydrogen atoms and nitrogen atoms, which can further enhance the adhesion with the cured resin film.

[0011] In the laminate according to the present invention, the resin of the cured resin film is preferably an acrylic resin, which can further increase transparency.

[0012] In the laminate of the present invention, the surface of the silicon oxide film includes a form in which the rate of change in haze value before and after the test is 2.0% or less when the Taber abrasion test is performed using a CS-10F wheel with a load of 500 g at 1,000 revolutions in accordance with JIS K 7204:1999 "Plastics - Abrasion test method using abrasive wheels," and the pencil hardness is 6H or more in the pencil hardness test in accordance with JIS K 5600-5-4:1999 "General test methods for paints - Part 5: Mechanical properties of coatings - Section 4: Scratch hardness (pencil method)."

[0013] The method for producing a laminate according to the present invention is a method for producing a laminate having a plastic substrate and a laminate film, the laminate film having a cured resin film and a silicon oxide-based film provided on the surface of the cured resin film, the method comprising the steps of: forming the cured resin film by applying a coating material for cured resin film containing inorganic crystal particles having an average particle size of 10 to 100 nm; and arranging a pair of electrodes opposed to each other perpendicularly to the surface of the cured resin film, applying a high-frequency voltage between the electrodes while supplying argon gas between the electrodes under an atmospheric pressure atmosphere to cause atmospheric pressure glow discharge of the argon gas, thereby generating plasmatized argon gas. and disposing the plastic substrate having the cured resin film on its surface downstream of the direction of ejection of the plasmatized argon gas from the two electrodes, and supplying a source gas consisting of an organosilicon compound for film formation and oxygen to an outer electrode region between the two electrodes and the cured resin film of the plastic substrate in a direction intersecting the flow of the plasmatized argon gas, thereby converting at least a portion of the source gas and oxygen into a plasmatized source gas and a plasmatized oxygen gas, which are then sprayed toward the surface of the cured resin film together with the plasmatized argon gas to form the silicon oxide-based film on the surface of the cured resin film. The thickness of the silicon oxide film is 0.05 to 1.00 μm. It is characterized by:

[0014] In the method for producing a laminate according to the present invention, the coating material for the cured resin film preferably contains silicone oil. The inorganic crystal particles are more likely to be localized on the silicon oxide film side, and more particles are embedded in the silicon oxide film, so that the adhesion between the cured resin film and the silicon oxide film is improved. As a result, the hardness and abrasion resistance of the laminate film can be further improved.

[0015] In the method for producing a laminate according to the present invention, the organosilicon compound is preferably at least one selected from the group consisting of trimethylsilane, tetraethoxysilane, tetramethoxysilane, and hexamethyldisiloxane, which can further enhance adhesion to the cured resin film. Effect of the Invention

[0016] According to the present disclosure, it is possible to provide a laminate having excellent transparency, hardness and abrasion resistance, and to provide a method for producing the laminate, the production process of which does not require reduced pressure, can be produced in a short time, and is low cost. [Brief description of the drawings]

[0017] [Figure 1] FIG. 2 is a schematic cross-sectional view showing an example of a laminate according to the present embodiment. [Diagram 2] 2 is a schematic diagram showing an example of the internal structure of a laminated film of the laminate shown in FIG. 1. [Diagram 3] FIG. 1 is a schematic diagram illustrating an example of a film forming apparatus. [Figure 4] 1 is a graph showing the results of Experimental Example 1. [Diagram 5] 1 is a schematic diagram of a surface of a substrate divided into areas in Experimental Example 2. FIG. [Figure 6] 6 is a graph showing the element abundance ratios on each line shown in FIG. 5 by XPS measurement. [Figure 7] 7 is a graph showing the abundance ratios of Si and O selected from the elements present in FIG. 6. [Figure 8] 13 is a graph showing the results of Experimental Example 3. [Figure 9] 1 shows the results for Example 1 of Experimental Example 4, where (a) is an SEM image showing the surface state after the formation of a cured resin film and before the formation of a silicon oxide-based film, (b) is an SEM image showing the surface state after the formation of the silicon oxide-based film and before the abrasion test, and (c) is an SEM image showing the surface state after the formation of the silicon oxide-based film and after the abrasion test. [Figure 10] 1 shows the results for Comparative Example 1 of Experimental Example 4, where (a) is an SEM image showing the surface state after the formation of a cured resin film and before the formation of a silicon oxide-based film, (b) is an SEM image showing the surface state after the formation of the silicon oxide-based film and before the abrasion test, and (c) is an SEM image showing the surface state after the formation of the silicon oxide-based film and after the abrasion test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Hereinafter, the embodiments of the present invention will be described in detail with reference to the drawings. Note that the present invention is not limited to the embodiments shown below. These implementation examples are merely illustrative, and the present invention can be implemented in various forms with various modifications and improvements based on the knowledge of those skilled in the art. Note that components with the same reference numerals in this specification and drawings are assumed to indicate the same components.

[0019] Fig. 1 is a schematic cross-sectional view showing an example of a laminate according to the present embodiment. Fig. 2 is a schematic view showing an example of an internal structure of a laminate film of the laminate shown in Fig. 1. As shown in Fig. 1, the laminate 1 according to the present embodiment is a laminate having a plastic substrate 10 and a laminate film 20. The laminate film 20 has a resin cured film 21 and a silicon oxide-based film 22 provided on the surface of the resin cured film 21. As shown in Fig. 2, the resin cured film 21 has inorganic crystal particles 30 with an average particle size of 10 to 100 nm. The inorganic crystal particles 30 are locally dispersed on the silicon oxide-based film 22 side and are further present at the interface between the resin cured film 21 and the silicon oxide-based film 22. The inorganic crystal particles 30 (30A) present at the interface are embedded in the silicon oxide-based film 22.

[0020] The laminate 1 is, for example, a member that can be used as a substitute for window glass for vehicles such as automobiles, trains, and aircraft. More specifically, the laminate 1 is a resin glazing that can be used as a substitute for glass for vehicle windows, etc., and is formed by laminating a coating layer that has excellent transparency, high hardness, and excellent abrasion resistance and scratch resistance on the surface of a transparent plastic material.

[0021] Conventionally, polycarbonate (PC) substrates have been suitably used as resin glazing for automobiles. However, the abrasion resistance of the PC substrate was about 50% in a Taber abrasion test, which was more prone to fogging than glass, which had a haze change rate of 1%, and was therefore unsuitable as a window material as is. When an acrylic resin was formed on the PC substrate by ultraviolet curing, the abrasion resistance was 2.5 to 10% haze change rate, which was still insufficient for a window material. Even when a silicon oxide film was formed directly on the PC substrate by atmospheric pressure plasma CVD, the abrasion resistance was about 2 to 10% haze change rate, which was still insufficient for a window material. This is thought to be mainly due to insufficient adhesion between the silicon oxide film and the PC substrate, and the silicon oxide film being thin, which caused the load during the abrasion test to be applied locally, resulting in deformation and shear stress. Therefore, in the laminate 1 of this embodiment, it has been discovered that by forming a laminate film 1 on a substrate, the laminate film 1 comprising a resin cured film containing a main resin such as an ultraviolet-curable acrylic resin and inorganic crystal particles 30, and a silicon oxide film provided on the resin cured film, a laminate that fully satisfies the transparency, hardness, abrasion resistance, and scratch resistance can be obtained.

[0022] The plastic substrate 10 is preferably transparent and is, for example, an acrylic resin such as polycarbonate, polymethyl methacrylate, or a polyester resin such as polyethylene terephthalate. Of these, the plastic substrate 10 is preferably a polycarbonate resin, which is suitable as an automobile glazing material.

[0023] The laminated film 20 preferably has a cured resin film 21 as an intermediate layer provided on the substrate, and a silicon oxide film 22 as an outermost layer provided on the surface of the cured resin film. The laminated film 20 may have other layers in addition to the cured resin film 21 and the silicon oxide film 22, as long as the effects of the present invention are not impaired.

[0024] The cured resin film 21 serves to improve weather resistance and adhesion of the silicon oxide film 22. The main resin constituting the cured resin film 21 is, for example, an acrylic resin, an acrylic urethane resin, an acrylic silicone resin, or an organosiloxane resin. In the laminate 1 according to this embodiment, the main resin constituting the cured resin film 21 is preferably an acrylic resin. This can further improve transparency.

[0025] The resin cured film 21 is preferably a photocured film containing a photocurable resin as a main resin, and the photocurable resin is preferably an ultraviolet-curable acrylic resin.

[0026] In the laminate 1 according to this embodiment, the cured resin film 21 preferably contains silicone oil. The inorganic crystal particles 30 are more likely to be localized on the silicon oxide film 22 side, and more particles are embedded in the silicon oxide film 22, so that the adhesion between the cured resin film 21 and the silicon oxide film 22 is improved. As a result, the hardness and abrasion resistance of the laminate film 20 can be further improved. The silicone oil is, for example, unmodified silicone oil or modified silicone oil. Of these, polyether-modified silicone is preferred.

[0027] The thickness of the cured resin film 21 is preferably 15 to 25 μm, and more preferably 18 to 23 μm. If the thickness of the cured resin film 21 is less than 15 μm, the weather resistance may be insufficient. If the thickness of the cured resin film 21 exceeds 25 μm, the adhesion between the cured resin film 21 and the plastic substrate, as well as the adhesion between the cured resin film 21 and the silicon oxide film 22, may decrease, resulting in peeling.

[0028] The inorganic crystal particles 30 are, for example, silicon oxide, aluminum oxide, or zirconium oxide. Of these, silicon oxide is more preferable. This can further increase the adhesion to the silicon oxide-based film 22. In addition, the transparency can also be further increased.

[0029] The inorganic crystalline particles 30 have an average particle size of 10 to 100 nm. If the inorganic crystalline particles 30 have an average particle size of less than 10 nm, they may be prone to aggregation and may not be uniformly dispersed. If the inorganic crystalline particles 30 have an average particle size of more than 100 nm, transparency may decrease. The inorganic crystalline particles 30 have an average particle size of more preferably 20 to 80 nm, and more preferably 30 to 70 μm.

[0030] The content of the inorganic crystal particles 30 relative to the mass of the main resin constituting the cured resin film 21 is arbitrary, but is preferably 10 to 50 mass %. If the content of the inorganic crystal particles 30 relative to the mass of the main resin constituting the cured resin film 21 is less than 10 mass %, the adhesion of the cured resin film 21 to the silicon oxide film 22 may be insufficient. Even if the content of the inorganic crystal particles 30 relative to the mass of the main resin constituting the cured resin film 21 exceeds 50 mass %, the adhesion of the cured resin film 21 to the silicon oxide film 22 may be insufficient. Furthermore, the weather resistance of the laminated film 20 may be insufficient.

[0031] The silicon oxide-based film 22 has a role of imparting transparency and improving hardness. In the laminate 1 according to this embodiment, the silicon oxide-based film 22 is preferably a plasma vapor deposition film under normal pressure. The plasma vapor deposition film under normal pressure is, for example, a film formed by providing sufficient oxygen in a plasma CVD method under normal pressure to plasmatize an organic silicon compound. The resin cured film 21 is etched by the plasma vapor deposition under normal pressure, and the inorganic crystal particles 30 contained in the resin cured film 21 are partially exposed, and more particles are embedded in the oxygen silicon-based film 22, so that the adhesion between the resin cured film 21 and the silicon oxide-based film 22 is further improved. As a result, the hardness and abrasion resistance of the laminated film 20 can be further improved.

[0032] In the laminate 1 according to the present embodiment, the silicon oxide film 22 contains oxygen atoms and silicon atoms, and preferably further contains at least one of carbon atoms, hydrogen atoms, and nitrogen atoms, which can further enhance the adhesion with the cured resin film 21.

[0033] In the laminate 1 according to this embodiment, the surface of the silicon oxide film 22 includes a form in which the rate of change in haze value before and after the test in a Taber abrasion test according to JIS K 7204:1999 "Plastics - Abrasion test method using abrasive wheels" is 2.0% or less when the test is performed at 1,000 revolutions with a CS-10F wheel and a load of 500 g, and the pencil hardness is 6H or more in a pencil hardness test according to JIS K 5600-5-4:1999 "General test methods for paints - Part 5: Mechanical properties of coatings - Section 4: Scratch hardness (pencil method)".

[0034] The thickness of the silicon oxide film 22 is preferably 0.05 to 1 μm, more preferably 0.05 to 0.8 μm, and even more preferably 0.05 to 0.3 μm. If the thickness of the silicon oxide film 22 is less than 0.05 μm, the wear performance may be significantly reduced. If the thickness of the silicon oxide film 22 exceeds 1 μm, peeling may occur.

[0035] As shown in FIG. 2, the inorganic crystalline particles 30 are locally dispersed on the silicon oxide-based film 22 side. In FIG. 2, the inorganic crystalline particles 30 are shown to have a circular cross-sectional shape, but in the present invention, the cross-sectional shape of the inorganic crystalline particles 30 is not limited thereto and may be an irregular shape. When the resin cured film 21 is divided into two in the thickness direction, with the lower layer 21a on the substrate side and the upper layer 21b on the silicon oxide-based film 22 side, it is preferable that the number of inorganic crystalline particles 30 present in the upper layer 21b is greater than the number of inorganic crystalline particles 30 present in the lower layer 21a. The fact that the inorganic crystalline particles 30 are locally dispersed on the silicon oxide-based film 22 side may be predicted, for example, by observing the surface state of the resin cured film 21 at a magnification of 1,000 to 20,000 times using a scanning electron microscope (SEM) and observing a sea-island structure in which the inorganic crystalline particles 30 form islands.

[0036] Furthermore, the inorganic crystal particles 30 are locally dispersed on the silicon oxide-based film 22 side, and are also present at the interface between the resin cured film 21 and the silicon oxide-based film 22, and the inorganic crystal particles 30 (30A) present at the interface are embedded in the silicon oxide-based film 22. The inorganic crystal particles 30 present at the interface between the resin cured film 21 and the silicon oxide-based film 22 are preferably, for example, in a form in which the inorganic crystal particles 30 are present across the resin cured film 21 and the silicon oxide-based film 22. It is preferable that the inorganic crystal particles 30 embedded in the silicon oxide-based film 22 are partly fixed to and integrated with the silicon oxide-based film 22, and it is more preferable that a part of the inorganic crystal particles 30 is fixed to the resin cured film 21 and the remaining part is fixed to the silicon oxide-based film 22. The fact that the inorganic crystal particles 30 are embedded in the silicon oxide-based film 22 can be indirectly confirmed by, for example, abrading the surface of the laminated film 20 with an abrasion tester to peel off a part or the whole of the silicon oxide-based film 22, and observing the peeled off portion of the silicon oxide-based film 22 with an SEM at a magnification of 1,000 to 20,000 times, finding that no sea-island structure of the inorganic crystal particles 30 is observed. This is presumably because the inorganic crystal particles 30 are embedded in the silicon oxide-based film 22, and when the silicon oxide-based film 22 is peeled off, the inorganic crystal particles 30 are also peeled off together with the silicon oxide-based film 22 due to the embedding.

[0037] Fig. 3 is a schematic diagram showing an example of a film forming apparatus. As shown in Fig. 3, the method for producing a laminate according to this embodiment is a method for producing a laminate having a plastic substrate 10 and a laminate film 20, in which the laminate film 20 has a resin cured film 21 and a silicon oxide-based film 22 provided on the surface of the resin cured film 21, and includes the following steps (1) and (2). (1) A step of forming a cured resin film 21 by applying a coating material for a cured resin film, which contains inorganic crystal particles 30 (shown in FIG. 2) having an average particle size of 10 to 100 nm. (2) A step of arranging a pair of electrodes 51 facing each other perpendicularly to the surface of the resin cured film 21, applying a high-frequency voltage between the electrodes 51 while supplying argon gas 56 between the electrodes 51 under atmospheric pressure, thereby causing atmospheric pressure glow discharge to convert the argon gas 56 into plasma and generating plasmatized argon gas, arranging a plastic substrate 10 having the resin cured film 21 on its surface downstream of the direction in which the plasmatized argon gas is sprayed from the electrodes 51, and supplying a source gas made of an organic silicon compound for film formation and oxygen to an outer region between the electrodes 51 and the resin cured film 21 of the plastic substrate 10 in a direction intersecting the flow of the plasmatized argon gas, thereby converting at least a part of the source gas and oxygen into a plasmatized source gas and a plasmatized oxygen gas, which are then sprayed toward the surface of the resin cured film 21 together with the plasmatized argon gas, thereby forming a silicon oxide-based film 22 on the surface of the resin cured film 21.

[0038] In the step of forming the cured resin film 21, the coating material for the cured resin film preferably contains at least a main resin and inorganic crystal particles 30 (shown in FIG. 2). When the cured resin film 21 is a photocured film, the coating material for the cured resin film preferably contains an ultraviolet absorber in addition to the main resin and the inorganic crystal particles 30 (shown in FIG. 3). The ultraviolet absorber is preferably an organic ultraviolet absorber such as a benzotriazole-based or triazine-based ultraviolet absorber. The coating material for the cured resin film may further contain various auxiliary agents such as a light stabilizer.

[0039] In the method for producing a laminate according to this embodiment, the coating material for the cured resin film preferably further contains silicone oil. The inorganic crystal particles 30 (shown in FIG. 2) are more likely to be localized on the silicon oxide film 22 side, and more particles are embedded in the silicon oxide film 22, so that the adhesion between the cured resin film 21 and the silicon oxide film 22 is improved. As a result, the hardness and abrasion resistance of the laminate film 1 can be further improved.

[0040] The method for forming the resin cured film 21 is not particularly limited, and for example, it is a method in which a coating material for ultraviolet cured film is applied onto the substrate 10 or a primer layer (not shown) provided on the substrate 10, dried, and cured by irradiating with active energy rays such as ultraviolet rays. The coating method is not particularly limited, and known methods such as a dip method, a flow coating method, a spray method, a bar coating method, a gravure coating method, a roll coating method, a blade coating method, an air knife coating method, a spin coating method, a slit coating method, and a microgravure coating method can be used.

[0041] In the step of forming the silicon oxide based film 22, for example, a film forming apparatus 50 as shown in Fig. 3 can be used. The film forming apparatus 50 shown in Fig. 3 is a remote atmospheric pressure plasma apparatus. The film forming apparatus 50 includes a pair of electrodes 51 arranged opposite to each other, an AC power source 52 that applies an AC voltage between the electrodes 51, an inert gas supply pipe 53 that supplies an inert gas 56, and a raw material gas supply pipe 54 that supplies a raw material gas for film formation.

[0042] The electrode 51 is, for example, a rectangular flat plate, and is made of a conductive material such as copper. The electrodes 51 are arranged parallel to each other at a predetermined distance, and are arranged perpendicular to the plastic substrate 10 having the resin cured film 21 as the film-forming body on its surface. The distance between the electrodes 51 is preferably 0.1 to 5.0 mm, and more preferably 0.3 to 2.0 mm. A dielectric 55 is arranged on the opposing surface of the electrode 51. The dielectric 55 is, for example, a plastic such as polytetrafluoroethylene, polyethylene terephthalate, or polyethylene, glass, or a metal oxide such as alumina.

[0043] The AC power supply 52 is a means for applying a high-frequency voltage, and is electrically connected to both electrodes 51. The AC power supply 52 is, for example, a high-voltage pulse power supply or an RF power supply. The high-frequency voltage is preferably 1 to 100 kV, and more preferably 10 to 15 kV. If the high-frequency voltage is less than 1 kV, the argon gas 56 may not be easily ionized. If the high-frequency voltage exceeds 100 kV, an arc discharge may occur. In addition, the frequency of the high-frequency voltage is preferably 1 kHz or more. When a voltage is applied between both electrodes 51 by the AC power supply 52, the region between both electrodes 51 becomes a plasma generation region 59 of a high electric field.

[0044] The inert gas supply pipe 53 is disposed with its nozzle facing the plasma generation region 59. The inert gas is argon gas. In this embodiment, the argon gas may be mixed with other inert gases such as helium gas as long as the effect of the present invention is not impaired. An argon gas cylinder is connected to the base end of the inert gas supply pipe 53.

[0045] The raw material gas supply pipe 54 is provided downstream of both electrodes 51 in the ejection direction of the argon gas 56 and upstream of the position where the film-formed body is placed in the ejection direction of the argon gas 56. The raw material gas supply pipes 54 are disposed facing each other along the lower surfaces of both electrodes 51. The distance between the ejection ports of the pair of raw material gas supply pipes 54 is preferably 1 to 10 mm, more preferably 2 to 5 mm. A raw material gas cylinder and an oxygen gas cylinder are connected to the base end of the raw material gas supply pipe 54. A raw material mixed gas 57, which is a mixture of the raw material gas and the oxygen gas, is supplied from the raw material gas supply pipe 54 to the outside-electrode region between both electrodes 51 and the resin cured film 21 of the plastic substrate 10 in a direction intersecting the flow of the plasmatized argon gas.

[0046] In the method for producing a laminate according to the present embodiment, the organosilicon compound is preferably at least one selected from the group consisting of trimethylsilane, tetraethoxysilane, tetramethoxysilane, and hexamethyldisiloxane, which can further increase the adhesion to the cured resin film 21.

[0047] The object to be coated is a plastic substrate 10 having a resin cured film 21 on its surface, and is placed with the resin cured film 21 facing the electrode 51 in a region outside the plasma generation region 59 downstream of the electrodes 51 in the direction of argon gas 56 ejection. At this time, the distance between the electrodes 51 and the surface of the resin cured film 21 is preferably 1 to 100 mm, more preferably 2 to 50 mm. If it is less than 1 mm, the coating range becomes too narrow, and it may take a long time to form the coating. If it exceeds 100 mm, the coating range is expanded, but the coating may become unstable.

[0048] The object to be coated is preferably placed on a conductor (not shown) made of a conductive material, such as a conductive metal such as copper, silver, or aluminum, or carbon.

[0049] The film forming apparatus 50 may further include a heater 58 for heating the film-forming body. Film forming accuracy can be improved by heating the film-forming body with the heater 58. The heating temperature by the heater 58 is preferably, for example, 40 to 300°C, and more preferably 50 to 250°C.

[0050] Next, a film forming method will be described.

[0051] First, while applying a high frequency voltage between the electrodes 51 by the AC power source 52, only argon gas 56 is supplied as an inert gas to a plasma generation region 59 of a high electric field from an inert gas supply pipe 53 under atmospheric pressure. This generates a glow discharge plasma, converts the argon gas 56 into plasma, and generates plasmatized argon gas. At this time, the flow rate of the argon gas 56 is preferably 100 to 5000 mm / sec, more preferably 300 to 4000 mm / sec. If the flow rate of the argon gas 56 is less than 100 mm / sec, the supply pressure of the argon gas is small, so that it is necessary to reduce the distance between the electrodes 51 and the film-forming body, and the film-forming range may be reduced. If the flow rate of the argon gas 56 exceeds 5000 mm / sec, the gas flow may be disturbed or abnormal discharge may occur. In this specification, "under atmospheric pressure" means that the film is formed under an open atmospheric pressure environment, and the pressure is preferably 0.5 to 2 atm.

[0052] While supplying argon gas 56, a raw material mixed gas 57 of raw material gas and oxygen gas is supplied from a raw material gas supply nozzle 54. As a result, at least a part of the raw material gas and oxygen becomes plasma raw material gas and plasma oxygen gas. The ratio of the supply amount of raw material gas 55 to oxygen gas is preferably 1:200 to 1:3000, more preferably 1:400 to 1:1000, in volume ratio. In addition, the total flow rate of raw material gas 55 and oxygen gas is preferably 50 to 2000 mm / sec, more preferably 150 to 1000 mm / sec. If the total flow rate of raw material gas 55 and oxygen gas is less than 50 mm / sec, film formation may not be performed due to a shortage of film raw material. If the total flow rate of raw material gas 55 and oxygen gas exceeds 2000 mm / sec, plasma formation may not be performed and film formation may not be performed.

[0053] The plasma source gas and the plasma oxygen gas flow further downstream under the flow pressure of the argon gas 56, and a silicon oxide film 22 is formed on the surface of the object to be coated (the surface of the resin cured film 21). When the object to be coated is large, the object to be coated is placed on a slidable mounting table, and the mounting table is slid as shown by the black bold arrow in FIG. 3 to sequentially form a film. At this time, the transport speed of the object to be coated is preferably 0.01 mm / sec or more, and more preferably 0.10 mm / sec or more. The upper limit of the transport speed of the object to be coated is not particularly limited, but is, for example, 5.00 mm / sec.

[0054] In the method for manufacturing a laminate according to the present embodiment, a resin cured film 21 is formed by adding inorganic crystal particles 30 such as silicon oxide crystal fine particles to a main resin such as an ultraviolet-curable acrylic resin, and then, by a remote plasma CVD method at atmospheric pressure, argon is used as an inert plasma gas, sufficient oxygen is provided to plasmatize an organic silicon compound, and a silicon oxide film is formed. The plasmatized argon gas has high kinetic energy and etches the cured product of the main resin. At this time, the surface of the resin cured film 21 is sputtered by the plasmatized argon, resulting in atomic level irregularities (phenomenon 1). Furthermore, the inorganic crystal particles 30 contained in the resin cured film 21 are partially exposed (phenomenon 2). At the same time as phenomena 1 and 2, a silicon oxide-based film 22 is formed. This process increases the adhesion area between the resin cured film and the silicon oxide film. Then, a laminated film structure in which the inorganic crystal particles 30 with very high hardness are embedded in the formed silicon oxide-based film 22 can be formed. As a result, the adhesion between the formed silicon oxide-based film 22 and the cured resin film 21 is greatly improved, and the embedded inorganic crystal particles 30, which have high hardness, serve to reduce abrasion of the silicon oxide-based film 22. Therefore, it has become possible to produce, at extremely low cost, a laminated structure that fully satisfies the transparency, hardness, abrasion resistance, and scratch resistance required for use, for example, as automobile glazing. EXAMPLES

[0055] The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples in any way.

[0056] Example 1 A resin cured film 21 was formed by coating the surface of a polycarbonate substrate (length 100 mm, width 100 mm, thickness 3.5 mm, manufactured by Mitsubishi Chemical Corporation) with a resin cured film paint prepared by Daikyo Nishikawa Co., Ltd., using an acrylic resin monomer as the acrylic resin raw material, and using an active energy ray polymerization initiator such as a UV absorber, a light stabilizer, and a UV polymerization initiator, and a surfactant, etc., as auxiliary raw materials, and dispersing silica particles (diameter approximately 50 μm). The coating was then dried at 100° C. to form a resin cured film 21.

[0057] Next, using the film-forming apparatus 50 shown in FIG. 3, a silicon oxide film 22 was formed on the surface of the cured resin film 21 under the following conditions. Electrode 51: Alumina plate (thickness 0.2 mm) Distance between electrodes 51: 1.2 mm High frequency voltage applied to electrode 51: frequency 30 kHz, voltage 11.5 kV Inert gas 56: Argon gas, flow rate: 500 mm / sec Raw material mixed gas 57: Trimethylsilane / oxygen gas: 0.5 / 250, total flow rate 250.5 mm / sec Distance between electrode 51 and the surface of resin cured film 21: 9 mm Conveying speed of the substrate 10: 0.1 mm / sec Film formation atmosphere: Open atmospheric pressure (101kPa) Heating by the heater 58 was not performed.

[0058] Example 2 A silicon oxide based film was formed in the same manner as in Example 1, except that the type of inert gas was changed from argon gas alone to a mixed gas of argon gas and helium gas (argon gas / helium gas=2 / 1).

[0059] Comparative Example 1 A silicon oxide based film was formed in the same manner as in Example 1, except that the type of inert gas was changed from argon gas only to helium gas only.

[0060] (Experimental Example 1) The laminates of the examples and comparative examples were evaluated for adhesion as follows. The adhesion was evaluated by measuring the critical peel load according to the scratch test method (JIS R3255:1997 "Test method for adhesion of thin films on glass substrates"), except that the substrate was changed to a laminate and the thin film was prepared by plasma CVD instead of vapor deposition. The critical peel load was shown as the adhesion. The results are shown in Table 1 and Figure 4.

[0061] [Table 1]

[0062] (Experimental Example 2) In Example 1, film formation was performed without transporting the substrate, and the effect of surface modification by plasmatized argon gas was confirmed. The results are shown in Figs. 5 to 7 and Table 2. Fig. 5 is a schematic diagram of the surface of the base material divided into areas in Experimental Example 2. In Fig. 5, dotted lines are area division lines, and have area division line numbers 1 to 11 in order from the left, such as 1, 2, . . . 8, . . 11 shown below. Fig. 6 is a graph showing the element abundance ratios by XPS measurement on each area division line shown in Fig. 5. Fig. 7 is a graph showing the abundance ratios of Si and O selected from the elements present in Fig. 6.

[0063] As shown in Figures 5 to 7 and Table 2, in the area directly below the film formation device (area between lines 2 to 8), the total abundance ratio of Si (silicon) and O (oxygen) was 50 atomic % or more, and it was confirmed that a silicon oxide-based film was formed. It is difficult to say that a silicon oxide-based film was formed in areas other than the area between lines 2 to 8, suggesting that film formation occurs only directly below the film formation device. On the other hand, in the area between lines 2 to 8 directly below the film formation device, the abundance ratio of O was higher than in other areas, and it was confirmed that surface modification was performed by plasmatized argon gas. In conclusion, it is considered that the area surface-modified by plasmatized argon gas and the area where a film is formed are the same area.

[0064] [Table 2]

[0065] (Experimental Example 3) An experiment was conducted to confirm that the inorganic crystal particles were dispersed locally on the silicon oxide film side as follows. The surface of the cured resin film was modified by applying plasma argon gas to the surface. The flow rates of the argon gas were 0 L / min, 1 L / min, 2 L / min, and 3 L / min. The results are shown in FIG. 8 and Table 3. FIG. 8 is a graph showing the results of Experimental Example 3. In FIG. 8 and Table 3, Si is derived from silicon oxide crystal fine particles or silicone oil, which are inorganic crystal particles in the cured resin film, and C is derived from acrylic resin, which is the main resin. As shown in FIG. 8 and Table 3, the sample with a flow rate of 1 L / min had a higher proportion of Si than the sample with a flow rate of 0 L / min. This is thought to be because impurities on the surface of the sample were removed by surface modification, and the surface of the sample was clearly visible. In addition, the samples with flow rates of 2 L / min and 3 L / min had a lower proportion of Si and a higher proportion of C than the sample with a flow rate of 1 L / min. The reason for this is believed to be that the sputtering effect of the argon plasma gas was stronger than when the flow rate was 1 L / min, causing the sample to be dug up. These results suggest that Si is localized on the surface of the silicon oxide film side of the cured resin film.

[0066] [Table 3]

[0067] (Experimental Example 4) An experiment was carried out to confirm that inorganic crystal particles present at the interface between the cured resin film and the silicon oxide film are embedded in the silicon oxide film, as follows. The laminates of Example 1 and Comparative Example 1 were subjected to an abrasion test, and the surface state after the abrasion test was observed by SEM at a magnification of 10,000 times. The abrasion test was carried out in accordance with JIS K 7204:1999 "Plastics - Abrasion test method using an abrasion wheel" using a Taber abrasion test with a load of 500 g, a CS-10F wheel, and 1000 revolutions. The results are shown in Fig. 9 and Fig. 10. Fig. 9 shows the results of Example 1 of Experimental Example 4, where (a) is an SEM image showing the surface state after the formation of the cured resin film and before the formation of the silicon oxide film, (b) is an SEM image showing the surface state after the formation of the silicon oxide film and before the abrasion test, and (c) is an SEM image showing the surface state after the formation of the silicon oxide film and after the abrasion test. 10 shows the results for Comparative Example 1 of Experimental Example 4, where (a) is an SEM image showing the surface state after the formation of the cured resin film and before the formation of the silicon oxide film, (b) is an SEM image showing the surface state after the formation of the silicon oxide film and before the abrasion test, and (c) is an SEM image showing the surface state after the formation of the silicon oxide film and after the abrasion test. The scale bars in the images are all 1 μm.

[0068] In the surface state after the formation of the cured resin film and before the formation of the silicon oxide film shown in FIG. 9(a) and FIG. 10(a), a sea-island structure was confirmed, suggesting that silicon oxide crystal fine particles were localized on the surface of the cured resin film. In the surface state after the abrasion test shown in FIG. 9(c) and FIG. 10(c), the part surrounded by the solid line is the part where the silicon oxide film was peeled off, and the part surrounded by the dashed line is the part where the silicon oxide film remained. In the part where the silicon oxide film was peeled off surrounded by the solid line in Example 1 shown in FIG. 9(c), the sea-island structure of silicon oxide crystal fine particles localized on the surface of the cured resin film seen before the formation of the silicon oxide film was not observed. From this, it is considered that the silicon oxide crystal fine particles are peeled off together with the silicon oxide film in the sample of Example 1, and it is suggested that the silicon oxide crystal fine particles (inorganic crystal particles) and the silicon oxide film are integrated, that is, the silicon oxide crystal fine particles (inorganic crystal particles) are embedded in the silicon oxide film. On the other hand, in the area of ​​the silicon oxide film peeled off in Comparative Example 1 surrounded by the solid line in Fig. 10(c), a sea-island structure of silicon oxide crystal fine particles localized on the surface of the resin cured film seen before the silicon oxide film was formed was observed. This suggests that in the sample of Comparative Example 1, only the silicon oxide film peeled off, and the silicon oxide crystal fine particles (inorganic crystal particles) and the silicon oxide film were not integrated, that is, the silicon oxide crystal fine particles (inorganic crystal particles) were not embedded in the silicon oxide film. The reason why the silicon oxide crystal fine particles (inorganic crystal particles) were embedded in the silicon oxide film in the film formation using plasma argon gas as in Example 1 is thought to be that argon has a larger atomic weight than helium, so the etching effect was large and surface modification occurred.

[0069] Example 3 A cured resin film 21 was formed on the surface of a polycarbonate substrate in the same manner as in Example 1. Next, a silicon oxide film 22 was formed on the surface of the cured resin film 21 using a film forming apparatus 50 shown in Fig. 3 under the following conditions. Electrode 51: Alumina plate (thickness 0.2 mm) Distance between electrodes 51: 1.2 mm High frequency voltage applied to electrode 51: frequency 30 kHz, voltage 11.5 kV Inert gas 56: Argon gas, flow rate: 250 mm / sec Raw material mixed gas 57: Trimethylsilane / oxygen gas: 0.25 / 313, total flow rate 313.25 mm / sec Distance between electrode 51 and the surface of resin cured film 21: 9 mm Conveying speed of the substrate 10: 0.1 mm / sec Scan count: 1 Film formation atmosphere: Open atmospheric pressure (101kPa) Heating by the heater 58 was not performed.

[0070] Example 4 A cured resin film 21 was formed on the surface of a polycarbonate substrate in the same manner as in Example 1. Next, a silicon oxide film 22 was formed on the surface of the cured resin film 21 using a film forming apparatus 50 shown in Fig. 3 under the following conditions. Electrode 51: Alumina plate (thickness 0.2 mm) Distance between electrodes 51: 1.2 mm High frequency voltage applied to electrode 51: frequency 30 kHz, voltage 11.5 kV Inert gas 56: Argon gas, flow rate: 500 mm / sec Raw material mixed gas 57: Trimethylsilane / oxygen gas: 0.5 / 313, total flow rate 313.5 mm / sec Distance between electrode 51 and the surface of resin cured film 21: 9 mm Conveying speed of the substrate 10: 0.1 mm / sec Number of scans: 2 Film formation atmosphere: Open atmospheric pressure (101kPa) Heating by the heater 58 was not performed.

[0071] Example 5 A cured resin film 21 was formed on the surface of a polycarbonate substrate in the same manner as in Example 1. Next, a silicon oxide film 22 was formed on the surface of the cured resin film 21 using a film forming apparatus 50 shown in Fig. 3 under the following conditions. Electrode 51: Alumina plate (thickness 0.2 mm) Distance between electrodes 51: 1.2 mm High frequency voltage applied to electrode 51: frequency 30 kHz, voltage 11.5 kV Inert gas 56: Argon gas, flow rate: 500 mm / sec Raw material mixed gas 57: Trimethylsilane / oxygen gas: 0.25 / 313, total flow rate 313.25 mm / sec Distance between electrode 51 and the surface of resin cured film 21: 9 mm Conveying speed of the substrate 10: 0.3 mm / sec Number of scans: 3 Film formation atmosphere: Open atmospheric pressure (101kPa) Heating by the heater 58 was not performed.

[0072] (Experimental Example 5) For the laminates of Examples 3 to 5, the haze change rate ΔH before and after the test was measured in a Taber abrasion test according to JIS K 7204:1999 "Plastics - Abrasion test method using abrasive wheels" using a load of 500 g and a CS-10F wheel at 1000 revolutions on the surface of the silicon oxide film. The results are shown in Table 4.

[0073] In Table 4, the deposition time is a value obtained when the transport speed of the substrate 10 is 0.1 mm / sec and the number of scans is 1, which is defined as deposition time 1. The rate is the film thickness formed when a given location is irradiated with plasma for 1 second, and is calculated by (film thickness [nm] ÷ deposition time) ÷ (electrode distance [mm] ÷ transport speed [mm / sec]).

[0074] [Table 4] [Explanation of symbols]

[0075] 1. Laminate 10 Plastic Substrates 20 Laminated Film 21 Resin cured film 22 Silicon oxide film 30 Inorganic Crystal Particles 30A Inorganic crystal particles present at the interface 51 electrode 52 AC power supply 53 Inert gas supply pipe 54 Raw gas supply pipe 55 Dielectric 56 Argon gas (inert gas) 57 Raw material gas mixture 58 Heater 59 Plasma generation region

Claims

1. A laminate having a plastic substrate and a laminate film, the laminated film has a cured resin film and a silicon oxide film provided on the surface of the cured resin film, the silicon oxide film having a thickness of 0.05 to 1.00 μm; the cured resin film contains inorganic crystal particles having an average particle size of 10 to 100 nm, the inorganic crystal particles being locally dispersed on the silicon oxide-based film side and also present at the interface between the cured resin film and the silicon oxide-based film; A laminate comprising inorganic crystal particles present at the interface, the inorganic crystal particles being embedded in the silicon oxide film.

2. The laminate according to claim 1 , wherein the cured resin film contains silicone oil.

3. 2. The laminate according to claim 1, wherein the silicon oxide film is a plasma vapor deposition film formed under normal pressure.

4. 4. The laminate according to claim 1, wherein the silicon oxide film contains oxygen atoms and silicon atoms, and further contains at least one of carbon atoms, hydrogen atoms, and nitrogen atoms.

5. 5. The laminate according to claim 1, wherein the resin of the cured resin film is an acrylic resin.

6. 6. The laminate according to claim 1, wherein the surface of the silicon oxide film has a haze value change rate of 2.0% or less before and after the test in a Taber abrasion test according to JIS K 7204:1999 "Plastics - Abrasion test method using abrasive wheels" when a load of 500 g is applied and a CS-10F wheel is used for 1,000 revolutions, and the pencil hardness is 6H or more in a pencil hardness test according to JIS K 5600-5-4:1999 "General test methods for paints - Part 5: Mechanical properties of coatings - Section 4: Scratch hardness (pencil method)".

7. A method for producing a laminate having a plastic substrate and a laminate film, comprising the steps of: the laminated film has a cured resin film and a silicon oxide film provided on a surface of the cured resin film, A step of forming the cured resin film by applying a coating material for the cured resin film, the coating material containing inorganic crystal particles having an average particle size of 10 to 100 nm; a step of disposing a pair of electrodes arranged opposite to each other perpendicular to a surface of the cured resin film, supplying argon gas between the electrodes in an atmospheric pressure atmosphere while applying a high frequency voltage between the electrodes, thereby generating plasmatized argon gas by atmospheric pressure glow discharge of the argon gas, disposing the plastic substrate having the cured resin film on its surface downstream from the electrodes in a direction in which the plasmatized argon gas is sprayed, and supplying a source gas consisting of an organosilicon compound for film formation and oxygen to an outer electrode region between the electrodes and the cured resin film of the plastic substrate in a direction intersecting the flow of the plasmatized argon gas, thereby forming at least a part of the source gas and oxygen into a plasmatized source gas and a plasmatized oxygen gas, which are then sprayed toward the surface of the cured resin film together with the plasmatized argon gas, thereby forming the silicon oxide based film on the surface of the cured resin film, The method for producing a laminate is characterized in that the thickness of the silicon oxide film is 0.05 to 1.00 μm.

8. The method for producing a laminate according to claim 7, wherein the coating material for forming a cured resin film contains silicone oil.

9. 9. The method for producing a laminate according to claim 7, wherein the organosilicon compound is at least one selected from the group consisting of trimethylsilane, tetraethoxysilane, tetramethoxysilane, and hexamethyldisiloxane.

Citation Information

Patent Citations

  • Coating composition

    JP1989306476A

  • Automobile resin window with protected surface

    JP2002036870A

  • Resin laminated body and manufacturing method of the same

    JP2008194993A

  • Transparent resin laminate and its production process

    JP2009067049A

  • Laminated form with hard coat layer

    JP2009286035A